Reduced Bone Loss Is Associated With Reduced Mortality Risk in Subjects Exposed to Nitrogen Bisphosphonates: A Mediation Analysis. (12th August 2019) - Bliuc, Dana; Tran, Thach; van Geel, Tineke; Adachi, Jonathan D; Berger, Claudie; van den Bergh, Joop; Eisman, John A; Geusens, Piet; Goltzman, David; Hanley, David A; Josse, Robert; Kaiser, Stephanie; et al.
ABSTRACT: Bisphosphonates, potent antiresorptive agents, have been found to be associated with mortality reduction. Accelerated bone loss is, in itself, an independent predictor of mortality risk, but the relationship between bisphosphonates, bone loss, and mortality is unknown. This study aimed to determine whether the association between bisphosphonates and mortality is mediated by a reduction in the rate of bone loss. Participants from the population‐based Canadian Multicentre Osteoporosis Study were followed prospectively between1996 and 2011. Comorbidities and lifestyle factors were collected at baseline and bone mineral density (BMD) at baseline and at years 3 (for those aged 40 to 60 years), 5, and 10. Rate of bone loss was calculated using linear regression. Information on medication use was obtained yearly. Bisphosphonate users grouped into nitrogen bisphosphonates (nBP; alendronate or risedronate) and etidronate and non‐users (NoRx) were matched by propensity score, including all baseline factors as well as time of treatment. Cox's proportional hazards models, unadjusted and adjusted for annual rate of bone loss, were used to determine the association between nBP and etidronate versus NoRx. For the treatment groups with significant mortality risk reduction, the percent of mortality reduction mediated by a reduction in the rate of bone loss was estimated using a causal mediation analysis. There were 271 pairs of nBP and matched NoRx and 327 pairs of etidronate and matched NoRx. nBP but not etidronate use was associated with significant mortality risk reduction (hazard ratios [HR] = 0.61 [95% confidence interval 0.39–0.96] and 1.35 [95% CI 0.86–2.11] for nBP and etidronate, respectively). Rapid bone loss was associated with more than 2‐fold increased mortality risk compared with no loss. Mediation analysis indicated that 39% (95% CI 7%–84%) of the nBP association with mortality was related to a reduction in the rate of bone loss. This finding provides an insight into the mechanism of the relationship between nBP and survival benefit in osteoporotic patients. © 2019 American Society for Bone and Mineral Research.